2015
DOI: 10.1016/j.lithos.2014.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Exhumation of an eclogite terrane as a hot migmatitic nappe, Sveconorwegian orogen

Abstract: We demonstrate a case of eclogite exhumation in a partially molten, low-viscosity fold nappe within high-grade metamorphosed crust in the Eastern Segment of the Sveconorwegian orogen. The nappe formed during tectonic extrusion, melt-weakening assisted exhumation and foreland-directed translation of eclogitized crust, and stalled at 35-40 km depth within the collisional belt. The eclogites are structurally restricted to a regional recumbent fold in which stromatic orthogneiss with pods of amphibolitized eclogit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 81 publications
1
83
0
Order By: Relevance
“…Weakening of rocks by interstitial melt plays a significant role in the dynamics of orogenic systems (e.g., Vanderhaeghe 2009;Jamieson et al, 2010) and can result in large displacements along melt-bearing shear zones bounding regions of rapid uplift (Hollister and Crawford, 1986), extrusion of lower crustal rocks along orogenic sutures (Konopásek and Schulmann, 2005;Möller et al, 2015), or channel flow of partially molten lower crust during intracrustal indentation (Beaumont et al, 2001;Vanderhaeghe et al, 2003;Culshaw et al, 2006;Jamieson et al, 2007;Schulmann et al, 2008a;Maierová et al, 2012). Labrousse et al (2015) suggested that melting of subducted upper continental crust at ultrahigh-pressure (UHP) conditions triggers its subsequent exhumation.…”
Section: Introductionmentioning
confidence: 99%
“…Weakening of rocks by interstitial melt plays a significant role in the dynamics of orogenic systems (e.g., Vanderhaeghe 2009;Jamieson et al, 2010) and can result in large displacements along melt-bearing shear zones bounding regions of rapid uplift (Hollister and Crawford, 1986), extrusion of lower crustal rocks along orogenic sutures (Konopásek and Schulmann, 2005;Möller et al, 2015), or channel flow of partially molten lower crust during intracrustal indentation (Beaumont et al, 2001;Vanderhaeghe et al, 2003;Culshaw et al, 2006;Jamieson et al, 2007;Schulmann et al, 2008a;Maierová et al, 2012). Labrousse et al (2015) suggested that melting of subducted upper continental crust at ultrahigh-pressure (UHP) conditions triggers its subsequent exhumation.…”
Section: Introductionmentioning
confidence: 99%
“…High-pressure metamorphism is lacking. This is in striking contrast to the 1.1-0.9 Ga Sveconorwegian orogen which comprises crustal-scale continental blocks displaced out of their original context, as well as deeply depressed, highpressure metamorphic parts of Baltica (Möller et al, 2015).…”
Section: The Hallandian Orogeny: Setting and Contextmentioning
confidence: 73%
“…1; Söderlund et al, 1999;Möller et al, 2007;Stephens et al, 2009;Petersson et al, 2013). Eclogite-facies metamorphism of parts of the Eastern Segment attests to deep tectonic burial (>55 km) of continental crust at 0.99-0.98 Ga (Möller, 1998(Möller, , 1999Johansson et al, 2001;Austin Hegardt et al, 2005;Möller et al, 2015). It was followed by high-grade metamorphism, ductile deformation and partial melting at 0.98-0.96 Ga (op.…”
Section: The 147-140 Ga Blekinge-bornholm Provincementioning
confidence: 99%
See 2 more Smart Citations